Ruthenium-catalyzed Olefin Metathesis in Water using Thermo-responsive Diblock Copolymer Micelles - Suzuki, Noriyuki; Watanabe, Ken; Takahashi, Chirika; Takeoka, Yuko; Rikukawa, Masahiro (Current Organic Chemistry, 2023)
Ruthenium-catalyzed olefin metathesis reactions were conducted in water with thermoresponsive block copolymers forming micelles. The block copolymers were prepared by living radical polymerization and consisted of a thermo-responsive and hydrophilic segments. The former segment included poly(N-isopropylacrylamide) or poly(N,N-diethylacrylamide), and the latter poly(sodium 4-styrene sulfonate), poly(sodium 2-acrylamido-2-methylpropanesulfonate) or poly(ethylene glycol). Homometathesis, cross-metathesis and ring-closing metathesis reactions proceeded to afford the products in moderate to good yields. Extraction efficiency from the reaction mixture was also studied.
Keywords: reaction in water